Control System Design and Simulation for Video Tracking - Altaei, Mohammed; Abdul Hakeem, Khassan; Hassan, Rana (Iraqi Journal of Science, 2024)
In this paper, a proposed video tracking system is introduced. The proposedsystem consists of two parts: motion estimation and tracking. Motion estimation iscarried out by computing the difference between two successive images. Thedifference is dark image contains small relatively brightness at the region ofexistence the moving object. The average location of the moving object in thedifference image is the target location, the tracking aims to make the head of camerafacing the target location. Such that, the relation between the head of the camera andthe target location relative to camera location is modeled to computes the deflectionin the head. The tracking part depends on the head deflection, which make thecontrol of camera motion toward the target location is modeled depending on thehead deflection with regarding continual and soft motion of the camera. Such motionis made by constraint the rate of changing the head of camera at each controlinterval. The simulation results show reality and acceptable motion of the camera,this ensures the efficiency of the tracking method and correct proposed model.